Spatio-temporal analysis of the environmental ranges and phenotypic traits of Zostera muelleri subpopulations in Central Queensland. (5th February 2023) - Andrews, Elizabeth L.; Irving, Andrew D.; Sherman, Craig D.H.; Jackson, Emma L.
Abstract: Intraspecific variation in phenotypic traits of seagrasses enables populations to tolerate varying environmental conditions and facilitates population persistence and expansion. Significant variation in seagrass population morphometrics may reflect highly plastic responses to abiotic and biotic factors, allowing populations to acclimate to changing environmental conditions. Alternatively, morphological variation may arise from developmental canalisation or genetically determined fixed traits, which may inhibit future plasticity and adaptive flexibility to changing environmental conditions. Understanding the drivers behind intraspecific variation in phenotypic traits is important for seagrass restoration practitioners when identifying populations that may provide suitable donor propagules with high adaptability to new sites or propagules that may be more resilient to future environmental changes. This study aimed to investigate whether variation in morphological traits of four subpopulations of Zostera muelleri on the Curtis Coast of the Great Barrier Reef World Heritage Area, Queensland, correlated with meadow-specific environmental conditions and whether this varied between seasons. Morphometric analysis was conducted on Z. muelleri apical shoots, sampled during the spring growing/flowering season and autumn senescent season. Meadow-specific environmental conditions were assessed using historical data dating back to 2008 and environmental simulation models developed for predicting wave, and light conditions. Results indicated that Z. muelleri subpopulations exhibited distinct morphologies throughout their seasonal growth cycle that may correlate with meadow-specific differences in sediment composition, hydrodynamic stress, and light availability. However, further investigation is required to understand if expressed morphological traits are reflective of environmentally driven phenotypic plasticity or genetically predetermined fixed traits (local adaptation or developmental canalisation). Knowledge gained from further studies into the drivers behind the observed variations in morphological traits would increase the understanding of the importance of trait-based selection of propagules for seagrass restoration meadows' resilience and persistence. Highlights: Morphometrics and meadow-specific environmental conditions of Zostera muelleri subpopulations were analysed.. Distinct morphological variations amongst subpopulations were detected throughout the seasonal growth cycle. Morphological variations may correlate with differences in sediment composition, hydrology, and light availability. Seagrass propagule trait-based selection may ultimately increase the success rate of seagrass restoration projects.